2008
DOI: 10.1016/j.yjmcc.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The Purkinje cell; 2008 style

Abstract: Cardiac Purkinje fibers, due to their unique anatomical location, cell structure and electrophysiologic characteristics, play an important role in cardiac conduction and arrhythmogenesis. Purkinje cell action potentials are longer than their ventricular counterpart, and display two levels of resting potential. Purkinje cells provide for rapid propagation of the cardiac impulse to ventricular cells and have pacemaker and triggered activity, which differs from ventricular cells. Additionally, a unique intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 81 publications
3
45
0
Order By: Relevance
“…Though identified in human PF cells, a lack of experimental data on I K(ACh) and I CaT prevents their inclusion in the current model, while the presence of I CaT in human PF cells has yet to be observed (Dun & Boyden 2008). The role of I NaL and I CaT has been studied in more detail in canine PF cells (O. V. Aslanidi et al unpublished data), which revealed that I CaT and I K(ACh) played a minor role, whereas the effect of I NaL on the APD was much more prominent.…”
Section: (C ) Limitationsmentioning
confidence: 99%
“…Though identified in human PF cells, a lack of experimental data on I K(ACh) and I CaT prevents their inclusion in the current model, while the presence of I CaT in human PF cells has yet to be observed (Dun & Boyden 2008). The role of I NaL and I CaT has been studied in more detail in canine PF cells (O. V. Aslanidi et al unpublished data), which revealed that I CaT and I K(ACh) played a minor role, whereas the effect of I NaL on the APD was much more prominent.…”
Section: (C ) Limitationsmentioning
confidence: 99%
“…Although fascicle system is composed of specific fibers with discrete conduction ability, activations could propagate with rapid speed. 14,15 Therefore, the initial stage of ILVT is always seen with the depolarization of conduction system. During SR, activation time between the distal ends of LAF and LPF is only a difference of 8.2 ms, and both fascicles contribute relatively equal to the depolarization of ventricle.…”
Section: Depolarization Of Fascicle System and Ventricle During Ilvtmentioning
confidence: 99%
“…These mechanical findings are in accordance with previous electric LQTS models reporting the longest APD in Purkinje cells and M cells located in the subendocardium and midmyocardium. 4,5,26 The APD of subendocardial Purkinje fibers in vitro has been reported to be even longer than in the M cells, but the delayed repolarization of the Purkinje system has failed to register on the ECG. 5 Purkinje cells are found in the His bundle and bundle branches and cover much of the endocardium.…”
Section: Mechanical Abnormalities In Lqts Patientsmentioning
confidence: 99%
“…2,3 The longest APD in LQTS models has been reported in endocardial Purkinje cells and in subendocardial to midmyocardial cells (M cells). 4,5 Transmural differences in APD have been considered to be of major importance in arrhythmogenesis in LQTS patients. 6 However, it has been challenging to assess APD and dispersion in patients.…”
mentioning
confidence: 99%